English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1)f(x)=arcsinx+arccosx
2) g(x)=(arcsin3x)/x

2007-03-19 17:58:49 · 2 answers · asked by aznboi4et3nity 1 in Science & Mathematics Mathematics

2 answers

f(x) = arcsin(x) + arccos(x)

The derivative of arcsin(x) is 1/sqrt(1 - x^2) and the deriative of arccos(x) is -1/sqrt(1 - x^2).

Therefore,

f'(x) = 1/sqrt(1 - x^2) + -1/sqrt(1 - x^2)
They are negations of each other, and thus
f'(x) = 0

{This implies arcsin(x) + arccos(x) is a constant.}

2) g(x) = arcsin(3x) / x

Using the product rule,

g'(x) = { [1/sqrt(1 - x^2)](3)[x] + arcsin(3x) } / x^2

To convert this from a complex fraction to a simple fraction, multiply top and bottom by sqrt(1 - x^2).

g'(x) = [ 3x + sqrt(1 - x^2) arcsin(3x) ] / [x^2 sqrt(1 - x^2) ]

From here we can rationalize the denominator and all that good stuff, but simplification techniques are second to knowing how to evaluate the derivative.

2007-03-19 18:14:38 · answer #1 · answered by Puggy 7 · 0 0

1. f(x) = arcsin x + arccos x

f'(x) = 1/ sqrt(1-x^2) + - 1/sqrt(1- x^2)

f'(x) = 0

2. g(x) = (arcsin 3x)/x

g'(x) = (x(1/sqrt(1-(3x)^2))(3) - arcsin 3x)/ x^2

g'(x) = (3x/sqrt(1-9x^2) - arcsin 3x)/ x^2

sorry, it looks a little wierd... it really looks better on paper....

2007-03-19 18:15:29 · answer #2 · answered by Paolo Y 2 · 0 0

fedest.com, questions and answers